Coupled optical-electrical-thermal analysis of a semi-transparent photovoltaic glazing façade under building shadow. (15th June 2021) - Wu, Jing; Zhang, Ling; Liu, Zhongbing; Wu, Zhenghong
Highlights: The real-time changing building eave shadow model is established. Use 3-D implicit finite difference to solve the temperature field of the PV system. A coupled optical-electrical-thermal model with building shadow is proposed. The I/V curve appears multi-knee shape due to the different shadow coefficient. The power generation and total heat gain have a reverse trend with eave width. Abstract: The semi-transparent photovoltaic glazing (STPVG) façade can introduce comfortable daylight into the indoor space and achieve energy efficiency, which is a promising PV glazing façade system. However, it is susceptible to building shadow, reducing power generation efficiency. This paper established a coupled optical-electrical-thermal model under dynamic changing building eave shadow of the STPVG façade and built a full-scale experiment platform to test and verify the coupled model. The model was then used to simulate and analyze the electrical performance and the temperature distribution of the STPVG under different eave shadow. The results show that the I/V curve appears multi-knee shape and the P/V curve appears multi-peak shape due to the different shadow coefficient in each PV string. Furthermore, the annual overall energy performance of STPVG in Changsha, China was compared with different eave width. The transmitted solar radiation, the energy generation and energy conversion efficiency, and the total heat gain decrease with the eave width increases in the months when the shadow appears. When the eave width is 0.29 m, the monthly largest transmission loss rate is in May at 3.86%; the largest energy generation loss rate is in April at 15.3%; and the largest indoor heat gain reduction rate is in August at 3.28%. This study can provide theoretical guidance for the system optimization and engineering application of the STPVG in building energy conservation.